A Key Molecular Regulator, RNA G-Quadruplex and Its Function in Plants - Liu, Haifeng; Chu, Zhaohui; Yang, Xiaofei (Frontiers in Plant Science, 2022)
RNA structure plays key roles in plant growth, development, and adaptation. One of the complex RNA structures is the RNA G-quadruplex (RG4) where guanine-rich sequences are folded into two or more layers of G-quartets. Previous computational predictions of RG4 revealed that it is widespread across the whole transcriptomes in many plant species, raising the hypothesis that RG4 is likely to be an important regulatory motif in plants. Recently, with the advances in both high-throughput sequencing and cell imaging technologies, RG4 can be detected in living cells as well as at the genome-wide scale. Here, we provide a comprehensive review of recent developments in new methods for detecting RG4 in plants. We also summarize the new functions of RG4 in regulating plant growth and development. We then discuss the possible role of RG4 in adapting to environmental conditions along with evolutionary perspectives.